2019
DOI: 10.25135/rnp.113.18.10.969
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Some Plants of the Asteraceae Family: Antiproliferative Activity of Psiadia punctulata Root Sesquiterpenes

Abstract: According to the World Health Organization Cancer is the second cause of death globally. The methanol extracts of fourteen Middle-Eastern plants of the family Asteraceae were screened for antiproliferative activity on five cancer cell lines (A2780, MCF7, HeLa, RKO and Jurkat) by using MTT assay. Psiadia punctulata (DC.) Vatke was selected for isolation and elucidation of the bioactive constituents by 1D-and 2D-NMR, and MS analyses. Flow cytometry was used to evaluate cell cycle analysis, apoptotic hallmarks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Aaronsohnia factorovskyi (A. factorovskyi ) is a member of Asteraceae family, which includes several medicinal plants, such as Matricaria chamomilla and Helianthus annuus (sunflower) that are characterized by their rich content of sesquiterpenes, flavonoids, and coumarins, which are active constituents of interesting therapeutic importance [ 4 ]. Recently, the flora of the Middle East has attracted the attention of several researchers and scientists to investigate their biological activities, particularly the antimicrobial and antitumor effects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aaronsohnia factorovskyi (A. factorovskyi ) is a member of Asteraceae family, which includes several medicinal plants, such as Matricaria chamomilla and Helianthus annuus (sunflower) that are characterized by their rich content of sesquiterpenes, flavonoids, and coumarins, which are active constituents of interesting therapeutic importance [ 4 ]. Recently, the flora of the Middle East has attracted the attention of several researchers and scientists to investigate their biological activities, particularly the antimicrobial and antitumor effects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous published study, we reported the marginal cytotoxic effect of the methanol extract of the aerial parts of A. membranacea on Jukart cells, with an IC 50 value of 60 ± 5.1 µg/mL [15]. That extract, however, did not exert any cytotoxic effect on MCF7 or A2780 cancer cell lines (IC 50 > 200 µg/mL) [23]. The growth of A2780 cells in this study was, however, significantly inhibited (IC 50 = 12.99 µg/mL) by A. membranacea EO, since the natural product components are generally considered cytotoxic when their IC 50 is ≤ 20 µg/mL [38].…”
Section: Discussionmentioning
confidence: 90%
“…Casticin, which was isolated from A. millefolium L. through HPLC, showed cytotoxic, early apoptosis, G 2 /M cell cycle arrest and consequently disruption of the mitotic spindle in two MCF7 sublines [22]. In a previous study, the methanol extract of A. membranacea exerted a moderate cytotoxic effect upon Jurkat cells (T-cell leukemia) using the MTT assay [23].…”
Section: Introductionmentioning
confidence: 96%
“…As described in the experimental section (supplementary material), the MTT test was performed against four cancer cell lines specifically MCF-7, Caco-2, MDA231, T47D, [17,18] and one normal cell line, namely skin Fibroblasts (PCS201012). [19,20] which was selected as a reference of normal cells to evaluate the safety of our products as reported in table 1.…”
Section: Mtt Assaymentioning
confidence: 99%